Latest Advancements in Transcutaneous Electrical Nerve Stimulation (TENS) and Electronic Muscle Stimulation (EMS): Revisiting an Established Therapy with New Possibilities - Patel P; Green M; Tram J; Wang E; Murphy M; Abd-Elsayed AA; Chakravarthy K (Journal of Pain Research)
Prachi Patel,1 Maja Green,2 Jennifer Tram,3 Eugene Wang,4 Melissa Murphy,5 Alaa a Abd-Elsayed,6 Krishnan Chakravarthy2 1Houston Methodist Willowbrook Hospital, Neuroscience Centre, Houston, Tx, USA; 2NXTSTIM INC. Department of Pain Medicine, San Diego, CA, USA; 3UCLA David Geffen School of Medicine/VA, Los Angeles, CA, 90095, USA; 4Timothy Growth, Pain Management and Chiropractic Care, Smithtown, NY, USA; 5North Texas Orthopedics and Spine Center, Grapevine, TX, 76051, USA; 6University of Wisconsin School of Medicine and Public Health, Health Sciences Learning Center, Madison, WI, 53705, USACorrespondence: Maja Green, Chief Scientific Officer, NXTSTIM Inc., Department of Pain Medicine, 5362 Sweetwater Trails, San Diego, CA, 92130, USA, Email mgreen@nxtstim.comAbstract: Transcutaneous Electrical Nerve Stimulation (TENS) and Electronic Muscle Stimulation (EMS) are non-invasive therapies widely used for pain relief and neuromuscular adaptation. However, the clinical research supporting the efficacy of TENS in chronic pain management is limited by significant methodological flaws, including small sample sizes and inconsistent reporting of stimulation parameters. TENS modulates pain perception through various techniques, targeting specific nerve fibers and pain pathways. High-frequency TENS is effective for segmental pain control, while low-frequency TENS, reliant on endogenous opioid pathways, may be less effective in opioid-tolerant patients. Additionally, TENS may influence autonomic functions, such as micro-perfusion and sympathetic tone, further broadening its therapeutic potential. EMS, on the other hand, enhances muscle strength and neuromuscular function, particularly in rehabilitation settings, by recruiting additional muscle fibers and improving neuromuscular efficiency. To address the limitations in existing clinical applications, future advancements in TENS and EMS technologies should focus on real-time optimization of stimulation parameters, consistent therapy delivery, and improved accessibility. Integrating automated and personalized adjustments can help streamline treatment, enhance patient compliance, and overcome traditional barriers to the effective implementation of these modalities. Additionally, developing systems that enable remote monitoring and customization of therapy protocols will expand the usability of TENS and EMS in diverse care settings. Future research must focus on rigorous study designs, standardized protocols, and meaningful patient-centered outcomes to fully realize the therapeutic potential of these modalities. Innovations like NXTSTIM EcoAI™ represent a significant advancement in delivering tailored, effective, and patient-friendly pain management and rehabilitation strategies.Keywords: chronic pain, TENS, EMS, neurotransmitters, gate control theory, central sensitization